Numerical investigation of severe slugging under conditions of a parabolic trough power plant with direct steam generation. (August 2016) - Hoffmann, A.; Hirsch, T.; Pitz-Paal, R.
Highlights: Simulation of severe slugging is successfully performed with the system code ATHLET. ATHLET predicts the period of severe slugging with a RMSE of less than 6% compared to experiments. Pressures above 60 bar do not show severe slugging for the investigated pipe geometries and flow conditions. Low relevance of severe slugging for direct steam generation process at typical operating pressures above 80 bar. Abstract: The present study reveals a numerical investigation of severe slugging with the system code ATHLET. It is aimed to close knowledge gaps about the two-phase flow within the connection pipes of two adjacent collectors in a solar thermal power plant with direct steam generation. The underlying ATHLET model provides a one-dimensional 6 equation model with a mass, momentum and energy equation for each phase, respectively. This comprehensive model provides all features for the examination of water steam flows in this type of power plants. A validation of ATHLET for severe slugging conditions is performed and the obtained periods of severe slugging as well as the pressure amplitudes are in good agreement with experimental data. The probability of severe slugging is studied for numerous flow conditions and geometric conditions which are close to the operation conditions and the piping system at the DISS test facility at the Plataforma Solar de Almería, Spain. Basically, larger vertical and downwards inclined pipe sections increase the probability of severe slugging. Severe slugging can be strongly suppressed by a high pressure operation. In a pipe geometry that shows easily severe slugging a pressure of P ⩾ 60  bar prevents severe slugging. In the case of a specific pipe geometry of the DISS test facility, a pressure of P ⩾ 30  bar is sufficient to have a non-oscillating flow behaviour.